Capacity of a Massive MIMO-OFDM system using Millimetric waves - Fernandes, Pedro Alexandre Velez (2017)
In modern day society, wirelesses communications are fundamental to the communications worldwide. But with the saturation of the usable spectrum for communications, the need for capacity is one of the most important challenges faced nowadays. With the development of technology, there is a much great need for quality of the service and bigger data streams. Increasing the capacity of a telecommuni-cation system will allow to cope with that need. The solution for the need for capacity, can be solved with the use of massive multiple input multiple output (MIMO) techniques, since MIMO system ap-proach have already shown to increase the capacity of a wireless system. The implications of this approach will make systems more complex and more energy consuming, in order to sustain the massive MIMO system. But such implementation combined with millimeter waves will allow the increase of the capacity of a system.